Seasonal changes in suicide in South Korea, 1991 to 2015 - Yang, Chi Ting (PLoS One, 2019)
Seasonality of suicidal behavior has been widely reported in many epidemiological studies with a well replicated suicide peak in spring followed by a trough in winter season. Research from some regions over the past few decades has shown a diminishing seasonal pattern of suicides and this introduced a new perspective on the suicide study. Data on all suicide deaths from the period 1991 to 2015 was extracted from the South Korean National Death Registration data set which was made available by Statistics Korea. Our findings confirmed a strong seasonal effect of suicides in South Korea throughout the study period and a marked diminishing pattern was observed since the period of 2006–2010. The rhythm of suicides kept changing across the time intervals with a spring peak followed by a second peak in late summer/autumn. The seasonality varied across age groups and the seasonal effect among the Korean elderly suicides was still found to be significant though a diminishing pattern was observed recently.